Artificial Cardiac Muscle with or without the Use of Scaffolds. (10th August 2017) - Li, Yifei; Zhang, Donghui
Abstract : During the past several decades, major advances and improvements now promote better treatment options for cardiovascular diseases. However, these diseases still remain the single leading cause of death worldwide. The rapid development of cardiac tissue engineering has provided the opportunity to potentially restore the contractile function and retain the pumping feature of injured hearts. This conception of cardiac tissue engineering can enable researchers to produce autologous and functional biomaterials which represents a promising technique to benefit patients with cardiovascular diseases. Such an approach will ultimately reshape existing heart transplantation protocols. Notable efforts are accelerating the development of cardiac tissue engineering, particularly to create larger tissue with enhanced functionality. Decellularized scaffolds, polymer synthetics fibrous matrix, and natural materials are used to build robust cardiac tissue scaffolds to imitate the morphological and physiological patterns of natural tissue. This ultimately helps cells to implant properly to obtain endogenous biological capacity. However, newer designs such as the hydrogel scaffold-free matrix can increase the applicability of artificial tissue to engineering strategies. In this review, we summarize all the methods to produce artificial cardiac tissue using scaffold and scaffold-free technology, their advantages and disadvantages, and their relevance to clinical practice.